Relationship between psychological factors and investment decision making: The mediating role of risk perception - Lubna Riaz; Ahmed Imran Hunjra (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The purpose of this study is to examine the role of various psychological factors which affect investment decision of Pakistani investors. A study model has been developed to describe the impact of risk propensity, asymmetric information, and problem framing on investor's behavior while making decisions through mediating role of risk perception. It also determines how much weight is attached to each independent variable by the investors when they make their decisions. The data for this study has been collected through an adapted questionnaire to determine the relationships between our variables. Structural Equation Modeling has been employed to determine the relationships among the variables. The findings and overall discussion concludes that the investor's behavior depends on how the available information is being presented to them and how much they are prone to taking risk while making decisions; thus playing a significant role in determining the investment style of an investor.
Keywords: 330; psychological factors; perception of risk; information asymmetry; risk propensity; investment decision making